ENSINO HÍBRIDO E METODOLOGIAS ATIVAS: NARRATIVAS, MEMÓRIAS, SABERES E FAZERES NO ENSINO DE GEOGRAFIA - Gandra, Aline Silva Buter (2021)
This study aims to reflect on the challenges and potential found in practices aimed at hybrid teaching and active methodologies in teaching Geography in public schools of basic education in the Metropolitan Region of Grande Vitória / ES. Therefore, supported by the research methodology of Oral History (BOM MEIHY, 1996), this research is appropriated from the narratives of seven teachers, not intending to unveil as limits, and possibilities of hybrid teaching and active methodologies. The theoretical framework that supports this investigation is anchored in the ideas of Moran (2015, 2018), Bacich, Tanzi Neto and Trevisani (2015), Bacich (2018) and Horn and Stalker (2015), with whom a research establishes dialogues in the narratives. interviewees, in order to support reflections on the potential of hybrid teaching and active methodologies as methodological alternatives for the teaching-learning process of Geography. The research indicated that hybrid teaching can open up multiple possibilities of work with active methodologies, enabling the student to become the protagonist of their learning process.